The synergistic antitumour effect of multi-components from Pulsatilla chinensis saponins in NCI-H460 lung cancer cell line through induction of apoptosis - Ziyi Guan; Lanying Chen; Yihan Zhou; Yingying Luo; Yaru Cui; Ronghua Liu; Binyao Shou (Taylor & Francis Group, 2020)
Context Pulsatilla chinensis (Bunge) Regel (Ranunculaceae) possess antitumour effects; however, its antitumour potential has not been extensively investigated. Objective To investigate the synergetic effect of multi-components from P. chinensis induced cell apoptosis and explore the mechanism. Materials and methods The cytotoxicity was measured against NCI-H460, SMMC-7721, HCT-116 and U251 cell lines treated with eight monomers from P. chinensis. The synergetic effect of a combination of Pulsatilla saponin D (PSD), Raddeanoside R13 (R13), and Pulsatilla saponin A (PSA) was assessed using CalcuSyn3.0. Annexin V-FITC/PI and DAPI staining analyzed apoptosis of NCI-H460 cells treated with PSD, R13 and PSA alone or in combination. Proteins differential expression was analyzed using proteomic, DAVID Bioinformatics Resources, R software environment and KEGG database, and verified by western blotting. Results PSD, R13, and PSA displayed greater antitumor activity with IC50 values of 5.6, 5.1 and 10.5 µM against NCI-H460 cells compared with other monomers. The combination of PSD, R13, and PSA had a synergistic effect at CI = 0.27 and induced 17.53% cells apoptotic detected by flow cytometric. Bioinformatic analysis showed an overview of the differentially expressed proteins and some signalling pathways. Moreover, some candidate proteins (LDHA, PI3K, NOL3 and cleaved-caspase-3) were validated by western blotting. Discussion and Conclusion These results show PSD, R13, and PSA are good candidates as natural products for use in the treatment of lung cancer. Potential signalling pathways and protein targets need to be further validated. The application of the drug combination approach also provides a therapeutic strategy for cancer.